ANALISIS SISTEM DAN METODE DISKUSI YANG DIGUNAKAN GURU DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS IV DI MIN 1 PALEMBANG - Mujila; Muhammad Faqih; Jeni Permata Sari; Muzdalifah Muzdalifah; Al Rois Mustaqim; Syarnubi; Padli (PAI RAFAH, 2024)
Learning systems and teaching methods are systems that are used as innovation to achieve learning goals. The aim of this research is to analyze the learning system and teaching group discussion methods used by religious education teachers in daily teaching. The research method used is a qualitative research method with a descriptive model. The data collection techniques used were interviews and observation. The research results were obtained by religious education teachers using teaching methods, namely lectures and active learning. This can be seen from the results of interviews and observations during the research process.